Rabies in Military Personnel: Epidemiology, Clinical Challenges, and Strategies for Prevention and Management - Elodie Monchatre-Leroy; Diana Isabela Costescu Strachinaru; Oula Itani; Sophie Wensierski; Alexandre Servat; Patrick Soentjens (Tropical Medicine and Infectious Disease, 2026)
For deployed military personnel, a single exposure from a rabies-infected animal can become a death sentence. With a case fatality rate approaching 100%, rabies remains a serious, yet insufficiently acknowledged hazard for service members, for whom prevention in operational environments poses unique challenges. We conducted a systematic literature search to identify relevant studies on rabies risk in armed forces personnel. By analysing rabies-related fatalities in the military, this review highlights the operational challenges posed by animal bites during deployment, including underreporting and delayed access to care, which compromise timely post-exposure prophylaxis (PEP) administration. Special emphasis is placed on prevention strategies, including pre-exposure prophylaxis (PrEP) and animal control protocols tailored to military settings. Its aim is to provide a comprehensive, evidence-based resource for healthcare professionals involved in the protection of deployed forces against this ancient yet still deadly infectious disease.